Blood on the Leaves / Blood on the Roots - Brendan Brown (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics)
This paper sets out to investigate the Nietzschean connection between Sylvia Wynter and Reiner Schürmann through a reading of Nietzsche’s On the Genealogy of Morals. Nietzsche’s account of ‘bad conscience’ is read through the Wynterian and Fanonian concept of ‘sociogeny’ to demonstrate its necessity to Nietzsche’s project of the Great Redeemer. This paper, then, demonstrates a previously undiagnosed influence of Nietzsche on Wynter and the role that anarchy plays in her construction of the ‘human being as praxis’. The essay concludes with an amelioration of Schürmann’s epochal genealogy to account for a racialized lacunae present in his Western genealogy of thought. It is by bringing all three together that we understand anarchy as being firmly committed to anti-racist and anti-anti-Black enactments. It concludes by highlighting the possibility of metaphysics after the withering of epochal archē in what this paper calls ‘the multitude of metaphysics’.